Underlying biological mechanisms of emotion dysregulation in bipolar disorder - Durdurak, Buse Beril; Morales-Muñoz, Isabel; de Cates, Angharad N.; Wiseman, Chantelle; Broome, Matthew R.; Marwaha, Steven (Frontiers in Psychiatry, 2025)
Difficulties with emotion regulation (ER) are a key feature of bipolar disorder (BD) contributing to poor psychosocial and functional outcomes. Abnormalities within emotion processing and regulation thus provide key targets for treatment strategies and have implications for treatment response. Although biological mechanisms and ER are typically studied independently, emergent findings in BD research suggest that there are important ties between biological mechanisms and the disturbances in ER observed in BD. Therefore, in this narrative review, we provide an overview of the literature on biological mechanisms underlying emotional dysregulation in BD including genetic and epigenetic mechanisms, neuroimaging findings, inflammation, hypothalamic-pituitary-adrenal (HPA) axis dysfunction, neuroplasticity and brain-derived neurotrophic factor (BDNF), and circadian rhythm disturbances. Finally, we discuss the clinical relevance of the findings and provide future directions for research. The continued exploration of underlying biological mechanisms in ED in BD may not only elucidate fundamental neurobiological mechanisms but also foster advancements in current treatment strategies and the development of novel targeted treatments.